Description of Student Responses Toward the Implementation of Problem-Based Learning Model in Physics Learning - Tanti Tanti; Dwi Agus Kurniawan; Weni Sukarni; Erika Erika; Roro Hoyi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
In essence, the orientation of the 2013 curriculum is an increase and balance between attitudes, skills, and cognitive competencies. However, the current learning process is generally teacher-centered. so that through the use of a learning model that is following the 2013 curriculum it is expected to be able to make the learning process student-centered. This research was conducted at SMA Negeri 8 Muaro Jambi on students of class X IPA 3 which aims to determine student responses when given a Problem-Based Learning model during the physics learning process. This research uses a mixed-method with an explanatory sequential design that combines quantitative and qualitative research systematically. Quantitative data in the form of a questionnaire student responses to problem-based learning model consisting of 20 statements and qualitative data in the form of interviews with students. Based on the results of the study it was found that the level of student response to the learning model was categorized quite well with a percentage of 56.5%. Based on the results of the study, it was found that the use of problem-based learning models in learning physics can increase student activity and improve student skills. This can be proven by seeing the students' responses in quite a good category. Through problem-based learning model students also feel responsible for formulating, analyzing, and solving problems. So that learning physics is more meaningful for students.